Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1103/physrevc.83.034615
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of low-lyingE1andM1strengths inTh232

Abstract: Properties of low-energy dipole states in232 Th have been investigated with the nuclear resonance fluorescence technique. The present work used mono-energetic γ-ray beams at energies of 2 -4 MeV from the high-intensity γ-ray source at Triangle Universities Nuclear Laboratory. Over 40 transitions corresponding to deexcitation to the ground state and first excited state were observed for the first time. Excitation energies, integrated cross sections, decay widths, branching ratios, and transition strengths for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(59 citation statements)
references
References 19 publications
4
54
0
1
Order By: Relevance
“…The impact of these new result on 18 F(p, α) 15 O reaction rate calculation and astrophysical consequences are presented in Ref. [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The impact of these new result on 18 F(p, α) 15 O reaction rate calculation and astrophysical consequences are presented in Ref. [20].…”
Section: Discussionmentioning
confidence: 99%
“…The spectroscopic information determined from these measurements are the excitation energies and the transferred angular momentum required to populate a given level in 19 Ne and 19 F. The angular distributions were compared to DWBA calculations to extract spectroscopic factors for all the wellpopulated states in the two nuclei. The astrophysical im- plications of the 18 F(d, n) study have been presented in a Rapid Communication [20]. The present paper describes the simultaneous study of the 18 F(d, n) and 18 F(d, p) reactions, including details of the analysis, and presents information on observed analog states in 19 Ne and 19 F. The present experimental approach provides direct determination of spectroscopic strength and new constraints on their spin and parity for the observed levels in 19 Ne near the proton threshold and represents the first successful multi-level spectroscopic application of the (d,n) reaction with a radioactive beam.…”
mentioning
confidence: 99%
“…One of the main uncertainties in this radioisotope's final abundance depends on its destruction rate via the (p,γ) and (p,α) channels. The 18 F(p,α) 15 O reaction is estimated to be a few thousand times faster [7] and therefore it has been the focus of many previous studies [8][9][10] (and references therein). Little effort has gone into the study of the 18 F(p,γ) 19 Ne reaction however, based on its much lower estimated cross section and the limited availability of sufficiently intense radioactive beams.…”
Section: B Previous Studiesmentioning
confidence: 99%
“…By contrast, a direct measurement of the 18 F(p,α) 15 O cross section [16] allowed the Γ p to be experimentally determined (Γ p =2.22±0.69 eV). A Γ p of 7.3±0.6 eV was extracted from proton transfer data [10], however, the population of the 330 keV resonance could have been contaminated by nearby states. 19 Ne studies by Laird et al [17] and Bardayan et al [18], respectively, found discrepancies in the spin and parity assignments for levels close to the proton threshold in 19 Ne.…”
Section: Thementioning
confidence: 99%
“…[6] for 156 Gd. Since then, scissors-type M1 excitations have been observed in many nuclei, including the most recent one in 232 Th [7]. The photon scattering facilities both at the S-DALINAC and HIGS at Duke University have produced and are still producing a wealth of data on the scissors mode and related phenomena.…”
Section: Introductionmentioning
confidence: 99%